THE OBSTACLE FACTORS OF MUSHARAKAH AND MUDHARABAH APPLICATION IN PAKISTAN - Khan, Muhammad Arsalan; Siswantoro, Dodik; Rahman, Abid Ur (UI Scholars Hub, 2020)
Islamic Banking is based on the Islamic financial system. It is a banking system whose fundamental rules and regulations are established on Shariah laws i.e., Islamic jurisprudence originated from the Quran and Sunnah of the Prophet Muhammad peace be upon him. Its functions must comply with Shariah rules and must not violate any Shariah principle. The Islamic finance system is based on Profit-loss sharing financing namely, Musharakah and Mudharabah but there are numerous issues and challenges faced by Islamic bank during the implementation of Musharakah and Mudharabah financing contracts. The various paper has been revealed some of the internal and external factors in this context, but the study is still unexplored in Pakistan. This paper aims to highlight those obstacles factors that affect the application of Musharakah and Mudharabah financing by Islamic Banks in Pakistan. This paper is based on the critical analysis of the related literature on the concepts of Profit-loss sharing based financing by Islamic Banks. The finding suggests 4 (four) main factors which hinder the application of Musharakah and Mudharabah by Islamic bank in Pakistan namely high risk, lack of awareness, Regulatory constraint and Low rate of return. Finally, this paper concludes by making recommendations that may be adopted by Islamic banks and regulators to facilitate the promotion of Musharakah and Mudharabah Financing.